The protection of cultural property in the event of armed conflict : commentary on the Convention for the Protection of Cultural Property in the Event of Armed Conflict and its Protocol, signed on 14 May 1954 in the Hague /: commentary on the Convention for the Protection of Cultural Property in the Event of Armed Conflict and its Protocol, signed on 14 May 1954 in the Hague. (2017) - Unknown
No abstract available